ANALYSIS OF PERSPECTIVE AND COMMUNITY BEHAVIOR IN MANAGEMENT OF FOREST AREAS WITH SPECIAL PURPOSE (KHdTK) UMM - Ahmad Ardiansyah; Tatag Muttaqin; Galit Gatut Prakosa (Journal of Forest Science Avicennia, 2020)
Forests are natural resources that have enormous benefits for the continuity of human life for now and in the future. The community around the forest has a big role in determining the sustainability of the forest because all community activities related to meeting the needs of daily life are very dependent on the existence of the forest. The people's behavior and actions are closely related to the community's perception of the forest. Communities in treating forests are also influenced by their experience and knowledge. Educational Forests or Special Purpose Forest Areas (KHdTK) are areas designated by the government for forestry research and development. University of Muhammadiyah Malang was appointed as the manager of Special Purpose Forest Areas (KHdTK) printed 43A, 44I, 44K-1, 44K-2, and 44L of Kedung Rejo RPH BKPH Pujon KPH Malang where the area is included in the status of production forest area and protected forest. This study aims to determine the perceptions of the surrounding community towards the plan to manage forest areas with specific objectives of UMM in plots 43A, 44I, 44K-1, 44K-2, and 44L, to determine the behavior of surrounding communities towards the plan to manage forest areas with UMM specific objectives in 43A plots, 44I, 44K-1, 44K-2, and 44L. The results of this study indicate that public perceptions of the KHdTK strategic plan by UMM were very well received. There is an inappropriate behavior of the community, namely the farming community in protected forest in 43A, but with prior approval from Perhutani, the behavior in managing the forest always considers the sustainability of the forest and the community always respects the applicable regulations, even though there is behavior that does not comply with the law but the community do that with the approval of Perhutani. The forest is the economic foundation of the surrounding community. In the future, UMM as the manager must be able to work together with the community and restore 43A plots according to their function, namely protected forests and rearranging farmers in KHdTK.